Factors related to intraoperative oxygen desaturation in geriatric patients in a Thai university hospital - Tamdee D. (2014)
Background: As a site of the Thai Anesthesia Incidents Study (THAI Study) of anesthetic adverse outcome, the authors continued the institutional data collection to determine the incidence of intraoperative oxygen desaturation of geriatric patients (age 65 years and over) and relative factors representing a Thai university hospital. Material and Method: Between July 1, 2003 and March 31, 2007, an anesthesia registry was conducted at King Chulalongkorn Memorial Hospital. Anesthesiologists and anesthesia residents were requested to record perioperative variables and adverse outcomes including oxygen desaturation (SpO2 ≤ 90% for 3 minutes or SpO2 < 85%) on a structured data record form. Univariable analysis was used to identify factors related to intraoperative oxygen desaturation. Multivariable generalized linear regression for risk ratio was used to investigate independent factors with significant association to intraoperative oxygen desaturation. A forward stepwise algorithm was chosen. A p-value < 0.05 was considered as statistically significant. Results: Among 54,419 cases in the registry, 8,905 geriatric patients underwent non-cardiac surgery receiving anesthesia. Among these, 21 patients developed intraoperative oxygen desaturation with an incidence of 23.6 (95% CI 10, 30):10000 anesthetics. Variables that predict intraoperative oxygen desaturation by multi-variable analysis were ASA physical status 3 [RR 4.6 (95% CI 1.6, 13.6)], ASA physical status 4-5 [RR 29.8 (95% CI 8.7, 102.8)], history of difficult airway [RR 13.1 (95% CI 1.7, 102.2)], recent respiratory failure [RR 6.0 (95% CI 1.2, 29.3)], and anesthetic agents used such as: pethidine [RR 6.2 (95% CI 1.9, 19.9)], and ketamine [RR 5.6 (95% CI 1.2, 25.9)]. Conclusion: The incidence of intraoperative oxygen desaturation of geriatric patients who underwent non-cardiac surgery in a Thai university hospital was 23.6:10000 anesthetics, which was comparable to others. The higher ASA physical status, history of difficult intubation and recent respiratory failure were risk factors of intraoperative oxygen desaturation. Pre-anesthetic evaluation particularly airway evaluation and identification of high-risk patients are crucial for prevention of oxygen desaturation.